Post Buckling Behavior of Prismatic Structural Steel Members with Semi Rigid Connections - Amer M. Ibrahim; Murtada A. Ismael (Engineering and Technology Journal, 2016)
In most designs of steel frames,beam-column connections are assumed either perfectly pinned or fully rigid. This assumption results in an incorrect estimation of the structural behavior of these frames. Practically, beam-column connections are between these two extreme assumptions and possess some rotational stiffness; therefore, it is called semi rigid connection. This research, presents a numerical analysis using finite element method to study the effect of semi-rigid connection on post buckling behavior of prismatic structural steel frames. The beam-column connection is modeled by linear elastic rotational spring element with specified rotational stiffness. The obtained results reveal that changing beam-column connection from rigid to semi rigid with different rotational joint stiffness values make the load-displacement curve of post buckling behavior less stiffer, the ultimate load decrease and ultimate vertical displacements increase with percentages depend on joint stiffness value and type of frame ;thus, semi-rigid connection should be considered in analysis and design of steel frames which exhibits post buckling behavior to obtain more realistic results.